Persistent Inflammation and Non-AIDS Comorbidities During ART: Coming of the Age of Monocytes - Bai, Ruojing; Li, Zhen; Lv, Shiyun; Wang, Ran; Hua, Wei; Wu, Hao; Dai, Lili (Frontiers in Immunology, 2022)
Monocytes are innate immune cells and serve as a fist line defender against pathogens due to engulfing and eliminating pathogens, or processing and presenting antigens to initiate adaptive immunity so as to promote immune responses. Monocytes are classified into classical, intermediate and non-classical monocytes, which play different roles in response to pathogens. Human immunodeficiency virus type 1 (HIV-1) infection breaks the balance among the monocyte subsets, and the number and function of monocytes will not be completely recovered after long-term antiretroviral therapy (ART). Monocytes are vital for the establishment and maintenance of HIV-1 latent viral reservoirs, and are closely related to immune dysfunction even after ART. Therefore, the present review focuses on the phenotypic function of monocytes and their functions in HIV-1 infection to elucidate their roles in HIV patients.